A Method of Direct Supervision for use with Group Employment Counsellors - Amundson, Norman E. (Canadian Journal of Counselling and Psychotherapy, 2011)
This paper outlines a method of direct supervision which has been applied to group employment counselling. To utilize this method effectively it is important to emphasize the development of a positive context, to minimize the intrusiveness of the observation, and to formulate the debriefing using a strength challenge format.